Self-Assembled Materials Incorporating Functional Porphyrins and Carbon Nanoplatforms as Building Blocks for Photovoltaic Energy Applications - Mao, Boyang; Hodges, Benjamin; Franklin, Craig; Calatayud, David G.; Pascu, Sofia I. (Frontiers in Chemistry, 2021)
As a primary goal, this review highlights the role of supramolecular interactions in the assembly of new sustainable materials incorporating functional porphyrins and carbon nanoplatforms as building blocks for photovoltaics advancements.